Genetic admixture history and forensic characteristics of Tibeto-Burman-speaking Qiang people explored via the newly developed Y-STR panel and genome-wide SNP data - He, Guanglin (2023)
Fine-scale patterns of population genetic structure and diversity of ethnolinguistically diverse populations are important for biogeographical ancestry inference, kinship testing, and development and validation of new kits focused on forensic personal identification. Analyses focused on forensic markers and genome-wide single nucleotide polymorphism (SNP) data can provide new insights into the origin, admixture processes, and forensic characteristics of targeted populations. Qiang people had a large sample size among Tibeto-Burmanspeaking populations, which widely resided in the middle latitude of the Tibetan Plateau. However, their genetic structure and forensic features have remained uncharacterized because of the paucity of comprehensive genetic analyses. Here, we first developed and validated the forensic performance of the AGCU-Y30 Y-short tandem repeats (STR) panel, which contains slowly and moderately mutating Y-STRs, and then we conducted comprehensive population genetic analyses based on Y-STRs and genome-wide SNPs to explore the admixture history of Qiang people and their neighbors. The validated results of this panel showed that the new Y-STR kit was sensitive and robust enough for forensic applications. Haplotype diversity (HD) ranging from 0.9932 to 0.9996 and allelic frequencies ranging from 0.001946 to 0.8326 in 514 Qiang people demonstrated that all included markers were highly polymorphic in Tibeto-Burman people. Population genetic analyses based on Y-STRs [RST, FST, multidimensional scaling (MDS) analysis, neighboring-joining (NJ) tree, principal component analysis (PCA), and median-joining network (MJN)] revealed that the Qiang people harbored a paternally close relationship with lowland Tibetan-Yi corridor populations. Furthermore, we conducted a comprehensive population admixture analysis among modern and ancient Eurasian populations based on genome-wide shared SNPs. We found that the Qiang people were a genetically admixed population and showed closest relationship with Tibetan and Neolithic Yellow River farmers. Admixture modeling showed that Qiang people shared the primary ancestry related to Tibetan, supporting the hypothesis of common origin between Tibetan and Qiang people from North China.